«Becoming parents as mending the past»: care-experienced parents and the relationship with their birth family. (May 2023) - Mauri, Diletta
Highlights: Becoming parents implies redefining the complex relationships with birth families. This process opens up to care-experienced parents new relational adjustments, but also several challenges. Care-experienced parents are able to cope in part by using skills learned within the Child Protection System. The key role of positioning/protecting vis-à-vis the birth family. The need to assuage concerns about the lack of an extended family for their children. Abstract: Objective: This paper studies how care-experienced parents, i.e. parents with a looked-after background, represent their relationship with the birth family. This relationship appears to be crucial in the intergenerational transmission of maltreatment and may enable an understanding of the dynamics that mediate its reproduction. Materials and methods: Constructivist Grounded Theory approach was used in this qualitative study. I conducted online in-depth semi-structured interviews with 17 care-experienced parents in Italy from May to November 2021. The interviews were analysed using open, focused and theoretical coding with the support of NVivo12 and the analysis itself was discussed with a board of care-experienced parents. Results: The relationship with the birth family is an aspect that frequently emerges in the interviewees' narratives. Birth family is represented through the more physical dimension of its presence in everyday life, as well as in the more symbolic one linked to one's inner experience. This means that birth family is crucial even when contacts are sporadic or no longer possible. Interviewees see parenting as an opportunity to create new relational adjustments, particularly in reference to their relationship with birth families. In fact, an internal daily dialogue and renegotiation with their own complex family history appears to take place. New parents compare their own childhoods with their children's, with this placing further pressure on the actual relationship with the birth family. In this process parents show interesting resources, possibly acquired within the child protection system. Conclusion: This study highlights relevant aspects of the relationship between the birth family and care-experienced parents. It represents a promising approach to a better understanding of the links affecting the intergenerational transmission of maltreatment, also vis-à-vis the role of the child protection system.